Multi-objective optimization of tooth surface based on minimum of flash temperature and vibration acceleration root mean square - Wang, Xigui; Wang, Yongmei; Shao, Junpeng; Liu, Yixiang; Zhou, Xue; Zhou, Mingli (Advances in mechanical engineering, 2018)
Marine ship gears are increasingly subject to strict requirements in terms of tooth surface load capacity, dynamic performance, vibration and noise generation, and so on. The optimization of tooth surface for improving gear comprehensive characteristics under various load bearing conditions is very important, and flash temperature and vibration acceleration root mean square values are highly related to the tooth surface carrying loads which are uniform or not. Optimal tooth surface for the minimum of flash temperature and vibration acceleration root mean square is very difficult to analytically determine due to the influence of multi-objective parameters discreteness. Satisfying design variables in multiple physical quantities leads to the minimum of multi-objective optimization. There, the minimum of flash temperature and vibration acceleration root mean square design is proposed, using the tooth contact analysis and load tooth contact analysis methods and multi-objective optimization. This research deals with the multi-objective optimization of tooth surface and its main purpose is to propose an approach to help design tooth corrections in order to simultaneously optimize several objective physical quantities.